Survey of Salmonellae occurrence in meat‐producing rabbitries in Switzerland. Issue 1 (22nd January 2022) - Schädler, Julia; Schwarz, Julia; Peter‐Egli, Judith; Schüpbach‐Regula, Gertraud; Wiederkehr, Danja; Albini, Sarah
Abstract: Background: An outbreak of salmonellosis due to Salmonella Typhimurium was detected coincidentally in a Swiss meat rabbitry, given that surveillance of Salmonella in rabbits is not mandatory in Switzerland. Methods: To assess the extent of potentially subclinical Salmonella carriage in meat rabbits, faecal pool samples of 50 farms (90% of Swiss commercial rabbitries) with ground covering litter and group housing were bacteriologically tested. Additionally, 236 rabbits showing clinical signs compatible with intestinal diseases, such as salmonellosis, were examined postmortem and analysed bacteriologically. Salmonella isolates were serotyped and analysed by whole genome sequencing (WGS). Results: Salmonella Typhimurium was detected in three commercial farms (6.0% of all tested farms). The affected farms were directly linked to the animal trade and Salmonella isolates were shown to be identical by WGS. Conclusion: There is no increased hazard for Salmonella carriage in the animal welfare‐friendly Swiss husbandry systems in general, despite risk factors such as ground covering litter.